Effect of Animated Health Education on Adolescents' Knowledge and Attitudes Toward Sexual Violence: A Time Series Study - Ririnisahawaitun; Apriani Susmita Sari; Suhaemi Suhaemi; Baiq Lastri Zuhria Astuti (PT.Mantaya Idea Batara, 2026)
Introduction: Adolescents are vulnerable to sexual violence. Violenceaffecting adolescents includes sexual violence in personal relationships, suchas dating, and sexual violence against children, with perpetrators often beingclose family members. Additionally, community violence can occur betweenfriends or in public locations. Health counseling on sexual violence canprevent this violence by enhancing adolescents' knowledge and attitudes aboutsexual violence. The study aims to determine the effect of health education onadolescents' knowledge and attitudes about sexual violence. This research isa quasi-experiment (pseudo-experiment) with a time series design. Thesample was 32 students at SMPN 1 Sakra, which was determined by clusterrandom sampling, so class VIIIB was chosen as the research sample. Healthcounseling on sexual violence was provided with animated video media. Dataprocessing with a paired t-test has tested the validity and reliability ofinstruments to measure adolescents' knowledge and attitudes about sexualviolence. This study's results showed there is an effect of health education onadolescents' knowledge and attitudes about sexual violence, with a p-value of0.000 each, where there is an increase in adolescents' knowledge about sexualviolence after being given education, with the difference between pretest andposttest being 2.72. After receiving education, adolescents' attitudes aboutsexual violence increase, showing a difference between the pretest andposttest of 3.75. The conclusion is that there is an effect of health educationon adolescents' knowledge and attitudes about sexual violence throughanimated video media.